Helicobacter pylori infection and inflammatory bowel diseases - Yu. P. Uspenskiy (Sankt-Peterburg : NIIÈM imeni Pastera, 2021)
Helicobacter pylori is detected in the human intestine on average in 35% of clinical cases, but the question about its etiopathogenetic role in intestinal diseases has not been fully investigated. Many scientists study a relationship between the H. pylori persistence and development of various bowel diseases. Diverse viewpoints have been proposed regarding a potential link between H. pylori and inflammatory bowel diseases (IBD). Here we review the data from domestic and foreign studies aimed at examining potential role of H. pylori both as a trigger and protector resulting in the pathogenetic alterations leading to developing Crohn‘s disease and ulcerative colitis. The former is favored by the hypothesis wherein H. pylori may trigger IBD due to potential connection between extragastric infection and its direct damaging action as well as indirect effects contributing to the initiation of oxidative stress, autoimmune aggression and development of intestinal dysbiosis. In addition, the effects of enterohepatic Helicobacter spp. promoting IBD pathogenesis are discussed. The mechanisms underlying the protective role of H. pylori infection may be driven via differentially expressed acute and/or chronic local inflammatory mucosal response able to downmodulate systemic immune responses and suppress autoimmune reactions, as well as skewing host immune response from a pro-inflammatory Th1/Th17 cell-mediated towards regulatory T-cell response. Moreover, it was found that H. pylori may induce production of antibacterial peptides counteracting potentially pathogenic bacteria involved in IBD pathogenesis. In particular, it was found that IBD patients are dominated with moderate active antral gastritis coupled to atrophy, with the peak intensity observed in patients under 30 years of age. Intensity of intestinal metaplasia in the gastric mucosa of IBD patients accounted for by the duration of the disease course. Basal IBD therapy with 5-aminosalicylic acid lowers severity and activity of gastritis, degree of atrophy as well as magnitude H. pylori invasion in the gastric mucosa. There is evidence that 5-aminosalicylic acid-containing drugs may result in a so-called “spontaneous eradication” of H. pylori infection. Extended investigations are required to examine a role of H. pylori in IBD pathogenesis.